Discovery of SRGA J144459.2-604207 with the SRG/ART-XC telescope: A well-tempered bursting accreting millisecond X-ray pulsar - Molkov, Sergey V.; Lutovinov, Alexander A.; Tsygankov, Sergey S.; Suleimanov, Valery F.; Poutanen, Juri; Lapshov, Igor Yu.; Mereminskiy, Ilya A.; Semena, Andrei N.; Arefiev, Vadim A.; Tkachenko, Alexey Yu. (EDP SCIENCES S A, 2025)
We report the discovery of the new accreting millisecond X-ray pulsar SRGA J144459.2-604207 using data of the SRG/ART-XC. The source was observed twice in February 2024 during the declining phase of the outburst. The timing analysis revealed a coherent signal near 447.9 Hz modulated by the Doppler effect due to the orbital motion. The derived parameters for the binary system are consistent with a circular orbit with a period of similar to ~5.2 h. The pulse profiles of the persistent emission, showing a sine-like part during half a period with a plateau in between, can be well modeled by emission from two circular spots that are partially eclipsed by the accretion disk. Additionally, during our observations with an exposure of 133 ks, we detected 19 thermonuclear X-ray bursts. All bursts have similar shapes and energetics, and none show any signs of an expanding photospheric radius. The burst recurrence times decreases linearly from similar to ~ 1.6 h at the beginning of observations to similar to ~2.2 h at the end and anticorrelate with the persistent flux. The spectral evolution during the bursts is consistent with the models of the neutron star atmospheres that are heated by accretion and implies a neutron star radius of 11-12 km and a distance to the source of 8-9 kpc. We also detected coherent pulsations during the bursts and showed that the pulse profiles differ substantially from those observed in the persistent emission. However, we could not find a simple physical model explaining the pulse profiles detected during the bursts.